Is the aquatic environment sufficiently protected from chemicals discharged with treated ballast water from vessels worldwide? – A decadal environmental perspective and risk assessment. (September 2018) - David, Matej; Linders, Jan; Gollasch, Stephan; David, Jan
Abstract: Ballast water managements systems (BWMS) installed on vessels may use active substances to inactivate or kill organisms in the ballast water. This paper provides new insights in this global issue - discharge of hazardous disinfection by-products with ballast water and related risk assessment for the environment. Considering the possible extent of this issue, the International Maritime Organization (IMO) engaged the Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection (GESAMP)-Ballast Water Working Group (BWWG) to oversee the evaluation process of BWMS that make use of active substances to prevent negative effects. We analysed all BWMS that received IMO final approval over a decade until 2017 and provide an overview of active substances used for ballast water treatment and disinfection by-products in the discharged ballast water. A risk assessment was conducted using the GESAMP-BWWG methodology for two very different commercial ports (Koper, Slovenia and Hamburg, Germany). Some relevant chemicals (chloropicrin, monochloroacetic acid, and dibromoacetonitrile) and other chemicals (isocyanuric acid and sodium thiosulphate) reached levels of concern, indicating a risk for aquatic organisms after discharge of that ballast water. From this analysis, it became clear GESAMP-BWWG worst-case scenario assumptions do not fully account for the potential environmental risks. We provide recommendations how to make this risk assessment more robust, recommend further research, and urge for policy as well as regulatory responses. Graphical abstract: Image 1 Highlights: Data regarding ballast water discharges of 42 ballast water management systems were studied. Active substances, disinfection byproducts, and neutralizers were summarized. Most of these substances may not cause unacceptable risk to the receiving environments. Some relevant and other chemicals risk reached levels of concern. Recommendations are provided to improve the risk assessment and approval process.